SILIH ASAH, SILIH ASIH, SILIH ASUH: Inspirasi Budaya Lokal untuk Gereja - Stephanus Djunatan (Litbang STFT Widya Sasana Malang, 2011)
Sundanese people are familiar with the traditional saying: silih asah, silih asih, silih asuh. This wise saying stands as an ethical principle to guide their attitudes in everyday life. This ethical principle is associated with 3 significant roles and their respective functions in Sundanese community, namely the reverend monk, the king and the father. These roles and their respective functions shape the Sundanese concepts of social relationship in a community, namely equality and functional interconnectivity. The Indonesian Catholic Church, especially in the Diocese of Bandung, can take into account the philosophical implications of this Sundanese saying in carrying out its mission. Bearing the principle of silih asah, silih asih, silih asuh in mind, the Church should proclaim the Good News through intensive involvements and caring services in local communities. This principle, in turn, helps the Church develop its identity properly in a local context